PENGARUH FINANCIAL GOVERNANCE, PERAN PERANGKAT DESA DAN KEJELASAN SASARAN ANGGARAN TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA Se-KECAMATAN MENGWI - Pratiwi Ni Kadek Novita; Kusumawati Ni Putu Ayu; Erlinawati Ni Wayan Alit (UNHI Press, 2022)
Accountability for managing village funds is defined by an obligation to carry out reporting and also accountability for the success or failure of the implementation of the organization's mission to fulfill or realize predetermined results, with media accountability carried out in a regular manner. Factors that influence the accountability of village fund management are financial governance, the role of village officials and clarity of budget targets. The sample in the study was 45 people consisting of the Village Head, Village Secretary, and Village Treasurer in all Mengwi District. The sampling technique in this study used a saturated sample, data was collected using a questionnaire. Data were analyzed by Validity Test, Reliability Test, Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Analysis, F Test, Coefficient of Determination Test and t Test. From the results of this study, financial governance, clarity of budget targets and the role of village officials have a significant and positive influence on the accountability variable for managing village funds in villages throughout Mengwi District..